A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships - Aguilera, Gastón; Mirande, Juan Marcos (Zootaxa, 2005)
Jenynsia tucumana new species is described from the upper Río Salí basin, province of Tucumán, northwestern Argentina. The new species is diagnosed by the possession of a row of dark markings ranging from dots to small vertical stripes from the tip of adpressed pectoral fin to the posterior margin of the hypural. Also, the new species has a mandibular canal pore W and a symmetrical fifth anal-fin ray in adult males; whereas the females lack a urogenital swelling. According to a phylogenetic reanalysis of the genus, the new species is sister to most species of the subgenus Jenynsia, except for J. onca and possibly J. sanctaecatarinae.